The Bible study handbook a comprehensive guide to an essential practice - Olesberg, Lindsay, 1966- (Downers Grove, Ill. : IVP Connect, 2012)
In The Bible Study Handbook Lindsay Olesberg lays a foundation for why we read the Bible, what attitudes and expectations are most helpful as we enter into serious Bible study, and what methods and practices yield the most fruit. --from publisher description
Foundations: Centrality of the word -- Power of the word -- Authority of the word -- Water for the soul -- Community around the word -- Building blocks: Honor the author -- Respect for the story -- Attentiveness -- Curiosity -- Understanding -- Response -- Tool box: Selection -- Creating a manuscript -- Prayer -- Determining genre -- Research tools -- Identifying structure -- Imagination -- Commentaries -- Studying poetry -- Group study. Appendix A: Tips for small group leaders -- Appendix B: Introduction to inductive Bible study -- Appendix C: Paying attention to the Bible -- Appendix D: Laws of composition--extended version -- Appendix E: Resources.
Includes bibliographical references.
Description based on print version record.
Keywords: Bible -- Hermeneutics; BIBLES / General; RELIGION / Biblical Reference / General; RELIGION / Biblical Reference / Handbooks; Electronic books